The reasons why children work on the streets: A sample from Turkey - KADIOĞLU, HASİBE (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The phenomenon of children worldng on the streets is a societal issue in all underdeveloped or developing countries just as it is in Turkey. The purpose of this research was to examine the reasons that children work on the street by conducting individual in-depth interviews with working children and their mothers, choosing individuals from similar socioeconomic demographic backgrounds and making a comparison of their acceptance or rejection of working, the perception of social support received by the mothers, and their problem-solving skills. The research was a mixed study that used both qualitative and quantitative techniques. The research was conducted in two stages. In the first stage, quantitative comparisons were made of the problem-solving skills of and social support received by the mothers of children working on the streets (n = 37) and non-working children (n = 35) and of the parental acceptance or rejection/control status of working children (n = 41) and non-working children (n = 41). In the second stage, the reasons children were working on the streets were evaluated qualitatively with seven children who were working on the streets and nine mothers. The Child/Adolescent Parental Acceptance-Rejection/Control Questionnaire, the Multidimensional Scale of Perceived Social Support, the Problem-Solving Inventory, and individual interview questionnaires were used as data collection tools. The social support and problem solving skills of the mothers with children working on the streets were lower than those of the mothers whose children were not working. The main themes and sub-themes that stood out at the end of the research were socioeconomic and political factors, environmental factors, cultural factors and family factors. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Street children; Social support; Problem solving; Turkey; LABOR